2016
DOI: 10.1002/jor.23139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human bone morphogenetic protein‐2 on a novel lung cancer spine metastasis model in rodents

Abstract: Lung cancer is the second most prevalent cancer. Spinal metastases are found in 30-90% of patients with death attributed to cancer. Due to bony destruction caused by metastases, surgical intervention is often required to restore spinal alignment and stability. While some research suggests that BMP-2 may possess tumorigenic effects, other studies show possible inhibition of cancer growth. Thirty-six athymic rats underwent intraosseous injection of lung adenocarcinoma cells into the L5 vertebral body. Cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…While a recent meta-analysis by Cahill et al 11 revealed that there was no conclusive evidence that BMP-2 was associated with the formation of cancer locally or at a distant site, there remains concern regarding its potential carcinogenicity. 58,62,63,66 Although the use of local bone grafts are relatively contraindicated following spinal column tumor resection, patients in 3 studies 19,41,54 received morselized local bone grafts. Of note, Coumans et al 19 reported the use of a vertebral autograft that contained tumor, after the diagnosis of benign intraosseous schwannoma was confirmed by intraoperative pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a recent meta-analysis by Cahill et al 11 revealed that there was no conclusive evidence that BMP-2 was associated with the formation of cancer locally or at a distant site, there remains concern regarding its potential carcinogenicity. 58,62,63,66 Although the use of local bone grafts are relatively contraindicated following spinal column tumor resection, patients in 3 studies 19,41,54 received morselized local bone grafts. Of note, Coumans et al 19 reported the use of a vertebral autograft that contained tumor, after the diagnosis of benign intraosseous schwannoma was confirmed by intraoperative pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,27,31,40 Additionally, although controversial, the application of bone morphogenetic protein-2 (BMP-2) to patients with tumors is generally contraindicated due to several prior studies that suggested an increased incidence of tumors in patients who received BMP-2. 58,62,63,66 Because of these issues, it is unclear what bone graft options should be selected in patients with spinal column tumors. The literature is also significantly limited, as a majority of prior reports were either retrospective with small numbers of patients, 1,36 or case reports, 5 focusing on survival outcomes or technical aspects of surgery rather than fusion outcomes.…”
mentioning
confidence: 99%
“…The emergence of bone metastasis indicates a shortened survival period and a serious decline in the quality of life of patients. In the treatment of lung cancer, the prevention and treatment of bone metastasis are also particularly important [ 5 ].…”
Section: Introductionmentioning
confidence: 99%